Oxidized Zirconium Bearing Surfaces in Total Knee Arthroplasty: Lessons Learned - Schüttler, Karl Friedrich; Efe, Turgay; Heyse, Thomas J.; Haas, Steven B. (The Journal of Knee Surgery, 2015)
Polyethylene wear in total knee arthroplasty is a still unsolved problem resulting in osteolysis and long-term failure of knee joint replacement. To address the problem of polyethylene wear, research aimed for an optimal implant design and for an optimal combination of bearing surfaces. Oxidized zirconium was introduced to minimize surface wear and thus potentially increase long-term implant survival. This review comprises the current literature related to in vitro and in vivo studies evaluating performance of oxidized zirconium total knee arthroplasty and results from retrieval analyses.
Keywords: oxidized zirconium; OxZr; total knee arthroplasty; knee osteoarthritis